ADOPTION OF THE TEACHING CAMPUS AS A STUDENT LEARNING MEDIA (Case Study of Students Participating in the Teaching Campus) - Yuni Tresnawati; Saeful Mujab; Anindita, Anindita; Muhamad Husni Mubarok (Bajang Institute, 2024)
The purpose of this research is to determine the process of spreading Teaching Campus Program innovations and the decision process for accepting (adopting) Teaching Campus Program innovations, especially at stage III. To realize the research objectives, this research uses qualitative research methods with a constructivist paradigm. Through the constructivist paradigm in question, researchers can describe social reality, through direct and detailed observations of Campus Teaching Program participants who utilize digital media naturally and see these activities in real life, creating a construction process by remembering and re-expressing experiences, the ability to compare and make decisions. from the results of interviews, and observations. The research results show that the diffusion process which includes relative, advantages, and compatibility elements strengthens the innovation adoption process. The decision process for accepting (adopting) the Campus Teaching Program III innovation goes through the same adoption stages based on the order of the 5 adoption stages proposed by Rogers, namely knowledge, persuasion, decision, implementation, and confirmation. The adopter category based on how quickly they accept the Campus Teaching Program III innovation is divided into four types, namely: innovators (innovators), early adopters (pioneers), early majority (followers), late majority (late followers).